Politics of Nationality and the Erosion of the USSR
XIV, 236 p.
Keywords: The Soviet Union has undergone many changes recently as many of its peoples are demanding autonomy and even independence. This volume of essays analyzes recent political and social movements and trends among a variety of Soviet ethnic groups and explains their grievances and goals.